Kemampuan Komunikasi Matematika Siswa Ditinjau dari Perbedaan Gaya Belajar Menurut David Kolb - Fatkhiyyah, I’aanatul; Winarso, Widodo; Manfaat, Budi (Jurnal Elemen, 2019)
The purpose of this study was to determine the distribution of student learning styles according to David Kolb's classification, to learn the average mathematical communication skills that have diverger learning styles, assimilators, convergers and accommodators, and to know whether or not there are significant differences in mathematical communication skills between students has a learning style diverger, assimilator, converger and accommodator. This research was conducted in MAN 2 Cirebon. The instruments used were the Learning style inventory (LSI) and mathematical communication skills tests. This type of research is a comparative study with a quantitative approach. Based on the results of data processing, the distribution of student learning styles included in diverger learning styles was 17% of students, assimilators were 27% of students, converger was 20% of students, and accommodators were 36% students. Using a scale of 0-50, the average mathematical communication ability of students is 28.63. Whereas when viewed from each distribution of learning styles, the ordinary mathematical communication skills of students diverger 12.80, students assimilator 32.88, student converger 44.17, and accommodator students 24.27. Based on the results of the analysis with the ANOVA test that there is a significant difference in students' mathematical communication skills between the learning style diverger, assimilator, converger and accommodator with a significant level of α = 5%.